Motive Forces: Accountants' Distinctive Values and Their Attitudes Toward Social Reforms - Madsen, Paul E.; Munch, Kevin; Nipper, Marvin (Contemporary Accounting Research, 2026)
ABSTRACT We use theory from identity economics, which synthesizes research characterizing how personal identity shapes decisions in domains such as education and career selection, to predict that the process by which people sort into accounting careers produces a population of accountants with a distinctive set of values. Specifically, we hypothesize that two kinds of personal values, called conservation values and self‐enhancement values, are overrepresented among accountants because they are associated with the decision to work as an accountant. Using data from 38 countries in the European Social Survey, we find support for both hypotheses. Given this evidence that accountants' values prioritize stability over change and concern for self over concern for others, we further hypothesize that, motivated by these values, accountants will be relatively skeptical about contemporary targets of social reforms, including those pursued by prominent accounting organizations. We test this prediction using attitudes about climate change and tolerance for minorities and find support for it. Based on our findings, we derive recommendations for an effective design of social reforms in the accounting profession. Our findings are relevant for accounting elites tasked with leading the profession into a dynamic future and contribute to the new and growing literature on accounting's human capital.